The kindred - Dow, Alechia (2022)
"Joy Abara knows her place. A commoner from the lowly planet Hali, she lives a simple life--apart from the notoriety that being Kindred to the nobility's most infamous playboy brings. Duke Felix Hamdi has a plan. He will exasperate his noble family to the point that they agree to let him choose his own future and finally meet his Kindred face-to-face. Then the royal family is assassinated, putting Felix next in line for the throne ... and accused of the murders. Someone will stop at nothing until he's dead, which means they'll target Joy, too"--
Joy Abara is a commoner from the lowly planet Hali, living a simple life-- apart from the notoriety that being Kindred to the nobility's most infamous playboy brings. Duke Felix Hamdi has a plan to exasperate his noble family to the point that they agree to let him choose his own future and finally meet his Kindred face-to-face. When the royal family is assassinated, Felix is next in line for the throne ... and accused of the murders. Someone will stop at nothing until he's dead, which means they'll target Joy, too. They steal a spacecraft and flee, crashlanding on a strange backward planet called Earth. --
Keywords: Inheritance and succession -- Juvenile fiction; Assassination -- Juvenile fiction; Nobility -- Juvenile fiction; Inheritance and succession -- Fiction; Assassination -- Fiction; Nobility -- Fiction; Man-woman relationships -- Fiction; Fantasy; Successions et héritages -- Romans, nouvelles, etc. pour la jeunesse; Assassinat -- Romans, nouvelles, etc. pour la jeunesse; YOUNG ADULT FICTION -- Science Fiction -- General; YOUNG ADULT FICTION -- Royalty; YOUNG ADULT FICTION -- Diversity & Multicultural; Assassination; Inheritance and succession; Nobility; Young adult fiction; Fictional Work; Science fiction; Fantasy fiction; Fiction; Juvenile works; Novels; Romance fiction; Young adult works; Science fiction; Novels; Romance fiction; Fantasy fiction; Science fiction; Romans